2020
DOI: 10.1016/j.chest.2019.10.053
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization of Severe Asthma Worldwide

Abstract: BACKGROUND: Clinical characteristics of the international population with severe asthma are unknown. Intercountry comparisons are hindered by variable data collection within regional and national severe asthma registries. We aimed to describe demographic and clinical characteristics of patients treated in severe asthma services in the United States, Europe, and the Asia-Pacific region. METHODS:The International Severe Asthma Registry retrospectively and prospectively collected data in patients with severe asth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
86
6
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 207 publications
(107 citation statements)
references
References 42 publications
7
86
6
8
Order By: Relevance
“…The patients frequently suffered from other co-morbid conditions in addition to AR, such as CRS, NP, and eczema, and tended to have late onset asthma. High co¼morbidity burden and late onset are features of severe asthma, 45 and indeed 13.1% of patients in our study had a confirmed diagnosis of severe asthma. This is likely an under-estimation; a recent analysis from the OPCRD showed that the majority of patients with severe asthma in primary care are 'hidden', and not referred to specialist care for a confirmed diagnosis.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The patients frequently suffered from other co-morbid conditions in addition to AR, such as CRS, NP, and eczema, and tended to have late onset asthma. High co¼morbidity burden and late onset are features of severe asthma, 45 and indeed 13.1% of patients in our study had a confirmed diagnosis of severe asthma. This is likely an under-estimation; a recent analysis from the OPCRD showed that the majority of patients with severe asthma in primary care are 'hidden', and not referred to specialist care for a confirmed diagnosis.…”
Section: Discussionsupporting
confidence: 63%
“…Severe asthma was noted in 13.1% (n ¼ 156) of patients (defined as those on GINA Step 5 treatment or with uncontrolled asthma on GINA Step 4) and over a quarter of patients had !2 asthma consultations (excluding annual review visit) in the year prior to MP-AzeFlu prescription (Table 2). Furthermore, 45.8% (n ¼ 544) of patients had !1 acute respiratory event, and 37.7% (n ¼ 448) had !1 asthma exacerbation. Only 9.6% (n ¼ 58/604) of patients had controlled asthma (GINA definition) in the baseline year (Table 3).…”
Section: Baseline Asthma Clinical Characteristics and Treatmentmentioning
confidence: 99%
“…reported the prevalence of nasal polyposis to be 7.3%. [ 13 ] Nasal polyposis has been reported to be associated with greater asthma severity;[ 39 ] hoever, we did not observe a significant difference in ACT scores between asthma patients with and without nasal polyps ( P = 0.5). Interestingly, we observed a significant difference in the prevalence of nasal polyposis between males and females ( P = 0.013), where males had a higher prevalence (56.9% vs. 43.1%, P = 0.013) which is in concordance with previously reported data.…”
Section: Discussioncontrasting
confidence: 54%
“…Allergic rhinitis was the most prevalent comorbidity in our cohort (52.2%) as observed in other severe asthma cohorts. [ 10 13 ] Allergic rhinitis is well knon to coexist with asthma and according to some authors more than 80% of asthmatics have a diagnosis of allergic rhinitis. [ 26 ] In addition, the presence of allergic rhinitis is thought to be associated with increased asthma severity.…”
Section: Discussionmentioning
confidence: 99%
“…Our study highlights that within the population of SANI registry, around one out of three patients were undergoing LAMA therapy; this is in line with what was reported by other national registries for severe asthma, with LAMA treatment being used in 13-45% of patients depending on the country. 32 That group was overall characterized by more severe disease in terms of lung function, exacerbations, patients' reported outcomes and required therapy; in fact, the prescription rate of biological agents, in particular anti-IL5 agents, and the use of systemic corticosteroids were higher in patients under LAMA therapy. Worthy of mention, the distribution of inflammatory biomarkers in that sub-population was very similar to the overall severe asthmatics population sample.…”
Section: Discussionmentioning
confidence: 99%